Precision Joining of Steel-Aluminum Hybrid Structure by Clinching Process - Ismail, M.I.S.; Buang, A.S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Clinching joining has become an alternative technique to conventional spot welding. This innovative joining technology can reduce the production costs and cycle times, and also offers a great prospective for a new product design and manufacturing. Without a better understanding on physical phenomena associated with the clinching process, the correcting unacceptable clinched joint is extremely costly and impossible for some cases. In this study, the overlap joining of low carbon steel and aluminum alloy in clinching process was experimentally and numerically investigated. The tensile-shear strength of overlap-clinched joints was evaluated by tensile-shear test. This test also was used to study the deformation and failure of clinched joints under tensile-shear loading. The results showed that the higher press load has a great influence for achieving better interlocking between steel-aluminum hybrid structures. Insufficient interlocking and thin neck thickness lead to the failure of clinched joints. It also was confirmed that the most critical region of the clinching tool located at the radius corner of punch and die. Development of simplified engineering approaches based on numerical simulation and correlations with experimental data could be very beneficial to industrial applications.